2018
DOI: 10.1016/j.ipej.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation of premature ventricular contractions originating from uncommon sites of right ventricle

Abstract: Premature Ventricular Contraction (PVC)/ventricular tachycardia (VT) with left bundle branch block (LBBB) morphology and inferior axis has been described classically to originate from the right ventricular outflow tract (RVOT). Some uncommon sites of idiopathic ventricular arrhythmia (VA) origins have been revealed including tricuspid annulus (TA) and right ventricular (RV) inflow free wall region. We present a series of two cases who have undergone electrophysiological study and successful radiofrequency abla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…PVC'S with an organic component need treatment as per guideline-directed medical therapy (GDMT) guidelines (4) . Since most of the PVC's are asymptomatic which barely requires any treatment (6) ,But few symptomatic Premature Ventricular beats might require medical therapy ,and for refractory and uncommon ectopic origin Electrophysiological Radio Frequency Ablation(EP-RFA) (7), (8) therapy is the mode of management .The success of EP-RFA ranges from 80%-95% (9) . Some studies showed PVC's association with Caffeine, Alcohol and even Intermittent fasting (9).…”
Section: Treatmentmentioning
confidence: 99%
“…PVC'S with an organic component need treatment as per guideline-directed medical therapy (GDMT) guidelines (4) . Since most of the PVC's are asymptomatic which barely requires any treatment (6) ,But few symptomatic Premature Ventricular beats might require medical therapy ,and for refractory and uncommon ectopic origin Electrophysiological Radio Frequency Ablation(EP-RFA) (7), (8) therapy is the mode of management .The success of EP-RFA ranges from 80%-95% (9) . Some studies showed PVC's association with Caffeine, Alcohol and even Intermittent fasting (9).…”
Section: Treatmentmentioning
confidence: 99%